Capital structure and business process management: evidence from ambidextrous organizations. Issue 5 (3rd September 2018) - Miglietta, Nicola; Battisti, Enrico; Carayannis, Elias; Salvi, Antonio
Abstract : Purpose: The purpose of this paper is to investigate the relationship between capital structure and business process management (BPM) within ambidextrous firms. In particular, referring to the listed companies in the Mercato Telematico Azionario (MTA) and Mercato degli Investment Vehicles (MIV) markets with large- and mid-sized capitalization, divided into ambidextrous and non-ambidextrous companies, the authors examined the capital structure to fill a gap in the current literature. Design/methodology/approach: This study uses a mixed-method sequential exploratory design. In particular, a qualitative study was conducted to identify some Italian-listed companies, called ambidextrous firms, which have implemented incremental (exploitative) and radical (explorative) innovations in an ambidexterity perspective of process management. A quantitative study was designed to provide insights into the different degrees of leverage of the listed companies selected by the qualitative analysis. Findings: The research is based on an empirical analysis undertaken with 69 companies listed on Italian markets (starting from the MTA and MIV Italy 100 – large- and mid-sized capitalization). In particular, the authors highlight 11 companies that, based on the literature, can be defined as ambidextrous organizations. These firms, in each year analyzed (2014, 2015, and 2016), have more leverage than non-ambidextrous ones. Considering that firms today need to constantly revisit their portfolio of debt and equity, ambidextrous organizations could evaluate the largest debt available in order to implement new BPM tools. Originality/value: To the authors' knowledge, this is the first exploratory study based on capital structure and the simultaneous exploration and exploitation of knowledge (ambidexterity) that also is informed by a BPM perspective. The paper presents evidence from Italian-listed companies that are referred to as ambidextrous and have different degrees of leverage.